Standard of care in advanced HIV disease: review of HIV treatment guidelines in six sub-Saharan African countries - Scheier, Thomas C.; Youssouf, Nabila; Mosepele, Mosepele; Kanyama, Cecilia; Adekanmbi, Olukemi; Lakoh, Sulaiman; Muzoora, Conrad K.; Meintjes, Graeme; Mertz, Dominik; Eikelboom, John W.; Wasserman, Sean (AIDS Research and Therapy, 2023)
Background: The World Health Organization (WHO) recommends an evidence-based package of care to reduce mortality and morbidity among people with advanced HIV disease (AHD). Adoption of these recommendations by national guidelines in sub-Saharan Africa is poorly documented. We aimed to review national guidelines for AHD management across six selected countries in sub-Saharan Africa for benchmarking against the 2021 WHO recommendations. Methods: We reviewed national guidelines from six countries participating in an ongoing randomized controlled trial recruiting people with AHD. We extracted information addressing 18 items of AHD diagnosis and management across the following domains: [1] Definition of AHD, [2] Screening, [3] Prophylaxis, [4] Supportive care, and [5] HIV treatment. Data from national guideline documents were compared to the 2021 WHO consolidated guidelines on HIV and an agreement score was produced to evaluate extent of guideline adoption. Results: The distribution of categories of agreement varied for the national documents. Four of the six countries addressed all 18 items (Malawi, Nigeria, Sierra Leone, Uganda). Overall agreement with the WHO 2021 guidelines ranged from 9 to 15.5 out of 18 possible points: Malawi 15.5 points, Nigeria, and Sierra Leone 14.5 points, South Africa 13.5 points, Uganda 13.0 points and Botswana with 9.0 points. Most inconsistencies were reported for the delay of antiretroviral therapy (ART) in presence of opportunistic diseases. None of the six national guidelines aligned with WHO recommendations around ART timing in patients with tuberculosis. Agreement correlated with the year of publication of the national guideline. Conclusion: National guidelines addressing the care of advanced HIV disease in sub-Saharan Africa are available. Besides optimal timing for start of ART in presence of tuberculosis, most national recommendations are in line with the 2021 WHO standards
Keywords: Advanced HIV disease; Standard of care; Sub-Saharan Africa; REVIVE trial; WHO